2020
DOI: 10.1101/2020.11.17.386300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Training with audio and video games improves audiospatial performance in a “cocktail-party” task: A controlled intervention study in young adults

Abstract: Computer game playing has been suggested to be an effective training to enhance perceptual and cognitive abilities. Focusing on potential improvements in auditory selective spatial attention induced by computer gaming, we compared a passive waiting-control group with two gaming groups, playing either a first-person audio-only action game requiring spatial attention and sound localization or a platform side-scroller video game without audiospatial components, which has been shown to improve cognitive performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Recent work on this topic has shown that various age groups profit from action video game training, showing enhanced performances in task switching abilities after playing for 3 weeks ( Basak et al, 2008 ; Strobach et al, 2012 ; Wang et al, 2016 ). Recently, Schuchert and Lewald (2020) , using a similar “cocktail-party” task as used here, demonstrated that both audio action game training and video non-action game training improved auditory selective spatial attention in younger adults. The present results thus suggest that a bimodal (audio-visual synchronous) game training may also be promising in this respect.…”
Section: Discussionmentioning
confidence: 76%
“…Recent work on this topic has shown that various age groups profit from action video game training, showing enhanced performances in task switching abilities after playing for 3 weeks ( Basak et al, 2008 ; Strobach et al, 2012 ; Wang et al, 2016 ). Recently, Schuchert and Lewald (2020) , using a similar “cocktail-party” task as used here, demonstrated that both audio action game training and video non-action game training improved auditory selective spatial attention in younger adults. The present results thus suggest that a bimodal (audio-visual synchronous) game training may also be promising in this respect.…”
Section: Discussionmentioning
confidence: 76%
“…Recent work on this topic has shown that various age groups profit from action video game training, showing enhanced performances in task switching abilities after playing for three weeks (Basak et al, 2008;Strobach et al, 2012;Wang et al, 2016). Recently, Schuchert and Lewald (2020), using a similar "cocktail-party" task as used here, demonstrated that both audio action game training and video non-action game training improved auditory selective spatial attention in younger adults. The present results suggest that a bimodal (audio-visual synchronous) game training may also be promising in this respect.…”
Section: Limitationsmentioning
confidence: 70%